Buzdağının Ötesi: Amerikan Board'un Kuruluşunda (1810-1825) ve İlk Faaliyetlerinde İngiliz Misyonerin Katkıları - (:unkn) unknown (My University, 2008)
Amerikan Board 1810'da Amerika'da kurulmuş bir misyonerlik teşkilatıdır. Türkiye'de yapılan araştırmalarda bu teşkilatın geçmişi hakkında, özellikle İngiliz misyonerlik cemiyetlerinin hem Amerikan Board'un kuruluş aşamasında hem de söz konusu teşkilatın Osmanlı Devleti'ndeki misyonerlik faaliyetleri sırasındaki katkıları hakkında yüzeysel bilgilere rastlanmaktadır.

American Board was found as a missionary society in America in 1810. Researches made in Turkey, there may be found rudimentary knowledge about the past of this society, especially the contributions of English missionary societies both at the initial phase of American Board and its missionary activities in Ottoman Empire. It is fact that however, American Board has got assistance from English missionary societies exceedingly. The purpose of this article is to display the corporation of the American missionaries with the English missionaries chiefly at the stage of beginning American Board. Thanks to all of this above mentioned, we endeavour to bring out the line of English missionary activities from England to America, India, Malta and Ottoman Empire. In this article, missionary reports will be handled as a main texts.
Beyond the Iceberg: The Contributions of English Missionaries in the Foundation (1810-1825) and First Activities of American Board
Keywords: Tarih